Ketogenic Diet for Obese COVID-19 Patients: Is Respiratory Disease a Contraindication? A Narrative Review of the Literature on Ketogenic Diet and Respiratory Function - Gangitano, Elena; Tozzi, Rossella; Mariani, Stefania; Lenzi, Andrea; Gnessi, Lucio; Lubrano, Carla (Frontiers in Nutrition, 2021)
Morbid obese people are more likely to contract SARS-CoV-2 infection and its most severe complications, as need for mechanical ventilation. Ketogenic Diet (KD) is able to induce a fast weight loss preserving lean mass and is particularly interesting as a preventive measure in obese patients. Moreover, KD has anti-inflammatory and immune-modulating properties, which may help in preventing the cytokine storm in infected patients. Respiratory failure is actually considered a contraindication for VLCKD, a very-low calorie form of KD, but in the literature there are some data reporting beneficial effects on respiratory parameters from ketogenic and low-carbohydrate high-fat diets. KD may be helpful in reducing ventilatory requirements in respiratory patients, so it should be considered in specifically addressed clinical trials as an adjuvant therapy for obese patients infected with SARS-CoV-2.